Klaus Wedekind - Charlotte Wedekind - Abuzeinab Musa: A Learner’s Grammar of Beja (East Sudan) - Grammar, Texts and Vocabulary (Beja-English and English-Beja) - Voigt, Rainer (Aethiopica, 2009)
Review